Eticidad democrática y lucha por el reconocimiento: una reconstrucción de la inluencia de Hegel en la democracia deliberativa - Pereira, Gustavo (2011)
“Democratic Ethical Life and the Struggle for Recognition: AReconstruction of Hegel’s Inluence on Deliberative Democracy”. Hegel’s politicalphilosophy represents a signiicant contribution to the understanding of moderndemocracy and social dynamics. As regards modern democracy, the concept ofdemocratic ethical life presented by Wellmer allows for the integration of equalsubjective rights and citizen participation in a deliberative culture that illsdemocracy with citizen vitality without going against individual liberties. As forsocial dynamics, they can be explained by the need for reciprocal recognition asthe key to the constitution of subjectivity, which explains the moral motivation inthe struggles of social groups. Both concepts are closely interwoven because thestruggle for recognition allows for an explanation of the dynamics of democraticethical life. Thus, democratic ethical life and the struggle for recognition, asinterwoven concepts, offer two key notions for the solution of some of the obstacleswith which contemporary political philosophy must deal.